Post a New Question

math

posted by on .

i am having a minor difficulty
i've been stuck for over an hour and don't know what to do
i don't know is this right

? = "+" or "-"
# = number

y=x
(x+1)squared + (y+1)squared = 6

i substitute y

(x+1)squared + (x+1)squared = 6
x squared + 2x + 1 + x squared + 2x + 1 = 6
2x squared + 4x + 2 = 6
2x squared + 4x - 4 = 0
2(x squared + 2x - 2) = 0
2(x ? #)(x ? #)

i get to here and now i am stuck
can u correct me if i did something wrong

please and thank you

  • math - ,

    You did nothing wrong, but not every quadratic factors.
    An easier way is not to expand it.
    from
    (x+1)^2 + (x+1)^2 = 6
    2(x+)^2 = 6
    (x+1)^2 = 3
    x+1 = ± √3
    x = -1 ± √3

    take it from here

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question